Relocations. - Saidon, Hasnul Jamal; Sitharan, Roopesh; Rajah, Niranjan (USM, 2008)
The initiative to present Hasnul Jamal Saidon and Niranjan Rajah as part of ISEA 08 comes from the need to highlight their contributions to the development of electronic art in Southeast Asia, as ISEA makes its regional debut. The exhibition is conceived under the ISEA 08 subthem of "locating media".